Gut Microbial Profile in Asymptomatic Gallstones - Song, Sen-Tao; Cai, Ling-Yan; Zeng, Xin; Xie, Wei-Fen (Frontiers in Microbiology, 2022)
There are few studies on the changes of gut microbiota in patients with gallstones, especially in patients with asymptomatic gallstones, and there are some deficiencies in these studies, for instance, the effects of metabolic factors on gut microbiota are not considered. Here, we selected 30 asymptomatic gallstone patients from the survey population, and 30 controls according to the age and BMI index matching principle. The 16SrDNA technology was used to detect and compare the structural differences in the gut microbiota between the two groups. Compared with healthy controls, the abundance of gut microbiota in patients with gallstones increased significantly, while the microbiota diversity decreased. At the level of phylum, both groups were dominated by Firmicutes, Bacteroides, Proteobacteria, and Actinobacteria. At the genus level, there were 15 species with significant differences in abundance between the two groups. Further subgroup analysis found that only unclassified Lactobacillales showed differences in the intestines of gallstones patients with hypertension, non-alcoholic fatty liver disease, or patients with elevated BMI (≧24). The structure of gut microbiota in patients with gallstones changed significantly, and this might be related to the occurrence of gallstones, rather than metabolic factors such as hypertension, non-alcoholic fatty liver disease, and obesity.